2010
DOI: 10.1002/ejic.201000272
|View full text |Cite
|
Sign up to set email alerts
|

Multistep Anchoring Route of Luminescent (5‐Amino‐1,10‐phenanthroline)tris(dibenzoylmethane)europium(III) on Si(100)

Abstract: A multistep route for the covalent anchoring of (5-amino-1,10-phenanthroline)tris(dibenzoylmethane)europium(III) molecules on silicon (100) has been developed. The anchoring route consists of Si functionalization with N-hydroxysuccinimide (NHS) activated carboxylic acid, followed by nucleophilic substitution at the carboxylic acid sites. Characterization of the resulting Si based hybrid materials was achieved by using several complementary techniques: X-ray photoelectron spectroscopy (XPS), attenuated total re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 84 publications
4
10
0
Order By: Relevance
“…The N 1s band consists of a peak centered at 400.0 eV, assigned to the nitrogen atoms of the phenanthroline ligand (Figure 6). 55 The Eu 3d XPS region shows the characteristic Eu 3d 5/2 –Eu 3d 3/2 doublet (at 1135.1 eV and 1164.8 eV, respectively) which is consistent with the presence of Eu III (Figure 6). 39,55 It is worth noting that a low‐intensity doublet can be observed at 1125.1 eV and 1155.1 eV, and this could indicate the presence of reduced Eu II 56.…”
Section: Resultssupporting
confidence: 62%
“…The N 1s band consists of a peak centered at 400.0 eV, assigned to the nitrogen atoms of the phenanthroline ligand (Figure 6). 55 The Eu 3d XPS region shows the characteristic Eu 3d 5/2 –Eu 3d 3/2 doublet (at 1135.1 eV and 1164.8 eV, respectively) which is consistent with the presence of Eu III (Figure 6). 39,55 It is worth noting that a low‐intensity doublet can be observed at 1125.1 eV and 1155.1 eV, and this could indicate the presence of reduced Eu II 56.…”
Section: Resultssupporting
confidence: 62%
“…[143] Often, the first step is the introduction of a functional group via a suitable organic molecule as self assembled monolayer (SAM) on a noble metal substrate, [230][231] silicon or silicon oxide surfaces [125] [127] or as coating ligand for nanoparicles. [152] After the introduction of a chemically addressable surface layer, efficient chemical conditions such as click chemistry [142][228] [232] or peptide coupling [119] have been applied to further diversify the exposed surface functionality.…”
Section: Platinum Electrode Modificationmentioning
confidence: 99%
“…Since AFM images do not have enough resolution to discern single molecules, AFL (contact mode) [27] has been used to evaluate the structure of the functionalized surface. [28] Thus, grafted molecules of 1 were removed by rastering different surface areas (0.5 ϫ 1.5 μm 2 ) with the AFM tip under a suitable constant force (0.24 μN). The thus obtained scratches have an average depth of 1.1 Ϯ 0.2 nm (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…or by considering a model, previously proposed, of a low density monolayer with silicon oxidation of the surface. [28] It has been observed that in these systems, SiO x islands (with thicknesses of around 1 nm) can intercalate organic molecules. [28] Since the SiO x islands that grow between the salen molecules cannot be scratched during ALF due to their greater hardness compared to organic molecules, [28] the overall scratch depth results obtained in these measurements are lower than the estimated length of 1.…”
Section: Resultsmentioning
confidence: 99%